2016
DOI: 10.1007/s00062-016-0519-y
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience with the TransForm Occlusion Balloon Catheter: Safety and Potential Advantages

Abstract: The TOBC was shown to be safe and effective for the treatment of intracranial aneurysms with BAC. In addition, it was successfully employed to perform angioplasty for vasospasm and BTO. Finally, it was used in the balloon anchor technique for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Giant aneurysms present unique challenges for achieving and maintaining access, including unfavorable angles between the inflow and outflow tracts, flow characteristics, and wide or complex necks. 2,6,7 Previously proposed techniques to maintain access while intra-aneurysmal looping are reduced or while the necessary larger catheters are advanced include balloons, 1,7,9,10 detachable coils, 2 stents, 6,1116 microwires, 17 stent retrievers, 18,19 and the rapid pull-back technique. 20 In this study, the results suggested that the Stabilizer could be used for multiple techniques while treating a giant aneurysm, including straightening of intra-aneurysmal looping, exchange for a stent delivery catheter, and advancement of an intermediate catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Giant aneurysms present unique challenges for achieving and maintaining access, including unfavorable angles between the inflow and outflow tracts, flow characteristics, and wide or complex necks. 2,6,7 Previously proposed techniques to maintain access while intra-aneurysmal looping are reduced or while the necessary larger catheters are advanced include balloons, 1,7,9,10 detachable coils, 2 stents, 6,1116 microwires, 17 stent retrievers, 18,19 and the rapid pull-back technique. 20 In this study, the results suggested that the Stabilizer could be used for multiple techniques while treating a giant aneurysm, including straightening of intra-aneurysmal looping, exchange for a stent delivery catheter, and advancement of an intermediate catheter.…”
Section: Discussionmentioning
confidence: 99%